Assessing academician attitude on online shopping: the analysis of technology acceptance model in MARA University of Technology (UiTM) City Campus, Malacca / Fatin Natasha Amir Hamzah - Amir Hamzah, Fatin Natasha (Faculty of Business and Management, 2017)
Internet has become one of the need to people around the world. Internet make it easier for people to socialize and doing business. Online shopping is one most popular trend that helps people to make online transaction anywhere and everywhere. People started to realize how convenience online shopping when they can shop from everywhere around the world without worries. This research mainly focusing on factors under Technology Acceptance Model (TAM) which is perceived ease of use, perceived usefulness and perceived risk that influence the academician attitude toward online shopping. In this study, regression analysis, correlation analysis and descriptive analysis was conducted to obtain information needed to complete this research. It involved acquiring data, preparing and distribute questionnaire to academician also analyzed the result. This study was conducted at MARA University of Technology (UiTM) City Campus, Malacca. This study revealed elements of Technology Acceptance Model (TAM) that influence academician attitude toward online shopping. The researcher has come out with several recommendations on how the study can be improve in the future.